2014
DOI: 10.1002/pc.22944
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Barium Titanate on poly(vinyl pyrrolidone)‐based composite polymer blend electrolytes for lithium battery applications

Abstract: Nanocomposite polymer blend electrolytes based on poly (ethylene oxide), poly (vinyl pyrrolidone) that contained lithium perchlorate as a dopant, propylene carbonate (PC) as a plasticizer and Barium Titanate (BaTiO3) as a filler were prepared for various concentrations of BaTiO3 using solvent casting technique. The structural and complex formations of the composite electrolyte membranes were confirmed by X‐ray diffraction and FTIR analysis. The addition of BaTiO3 nanofillers improved the ionic conductivity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
0
21
0
Order By: Relevance
“…It is well-known that a shift to lower wavenumbers and an increase in the intense of ν(CO) are associated with an increase in the polarity of the CO groups, which is ascribed to the presence of ethereal functional groups coordinating Li + cations. [30][31][32] These findings indicate that during charge-discharge process, the LCO particles transport Li + cations by coordinating CO functional group in PEO chains. Combined with observed continuous film of LCO-PEO composite cathodes, it is suggested that the formed 3D continuous ionic conductive network among the LCO particles promotes the Li + ion transportation via coordinating CO functional group in PEO chains thus enhancing the specific capacity of ASLBs.…”
Section: Resultsmentioning
confidence: 82%
“…It is well-known that a shift to lower wavenumbers and an increase in the intense of ν(CO) are associated with an increase in the polarity of the CO groups, which is ascribed to the presence of ethereal functional groups coordinating Li + cations. [30][31][32] These findings indicate that during charge-discharge process, the LCO particles transport Li + cations by coordinating CO functional group in PEO chains. Combined with observed continuous film of LCO-PEO composite cathodes, it is suggested that the formed 3D continuous ionic conductive network among the LCO particles promotes the Li + ion transportation via coordinating CO functional group in PEO chains thus enhancing the specific capacity of ASLBs.…”
Section: Resultsmentioning
confidence: 82%
“…From elemental mapping by field‐emission scanning electron microscopy (FE‐SEM), it is clear that LiClO 4 was uniformly distributed in these COFs (Supporting Information, Figures S12–S14). Upon loading LiClO 4 , FTIR spectra revealed a new peak at 625 cm −1 , which was assigned to the ClO 4 − anion (Supporting Information, Figures S2–S4, red curves) . To confirm the thermal stability, we conducted the TGA analysis of Li + @TPB‐DMTP‐COF.…”
Section: Resultsmentioning
confidence: 99%
“…BaTiO 3 , Al 2 O 3 , TiO 2 , MgO and SiO 2 ) and other fillers (e.g. carbon nanotube (CNT) and graphene oxide (GO)) leads to the enhancement of the ionic conduction . Suriani and Mohd reported that the ionic conduction of a PEO‐based electrolyte can reach 1 mS cm −1 by introduction of 0.35 wt% CNT filler into a SPE structure.…”
Section: Introductionmentioning
confidence: 99%
“…carbon nanotube (CNT) and graphene oxide (GO)) leads to the enhancement of the ionic conduction. 24,27,28 Suriani and Mohd 29 reported that the ionic conduction of a PEO-based electrolyte can reach 1 mS cm −1 by introduction of 0.35 wt% CNT filler into a SPE structure. Tang et al 30 reported an ionic conductivity of about 1.5 mS cm −1 by the addition of packaged CNT particles between clay layers.…”
Section: Introductionmentioning
confidence: 99%